Re-imaging election : divine election as representing God to others and others to God - McDonald, Suzanne, 1973- (Cambridge, U.K. ; Grand Rapids, Mich. : Wm. B. Eerdmans Pub., 2010)
Here is a fresh look at one of the Reformed tradition's most controversial and defining doctrines: election. In conversation with John Owen and Karl Barth, Suzanne McDonald argues that acknowledging the significance of "representation"-- representing God to others and others to God -- is key to understanding the nature and purpose of election. Re-imaging election investigates anew the scriptural contours of election and, especially, the prominent role of the Holy Spirit. Election, McDonald says, is not only "in Christ" but also "by the Spirit."
I. Posing a pneumatological problem. Election, the image, and the spirit : John Owen -- Election, the image, and the spirit : Karl Barth -- Election "in Christ" in Barth : some pneumatological queries -- II. Re-presenting the image; re-imaging election. Sketching some scriptural contours -- Election, the Spirit, and the ecclesial imago Dei -- III. Election to representation in dialogue. Some problems, a parable, and the parousia -- Owen and Barth : beyond the impasse -- Epilogue: Glancing backward, looking forward.
Revision of author's thesis (Ph. D.)--University of St Andrews, 2006 under title: Re-imaging election : the Holy Spirit and the dynamic of election to representation.
Includes bibliographical references (p. 202-209) and index.
Keywords: Election (Theology) -- History of doctrines; Reformed Church -- Doctrines -- History -- 17th century